Enhanced Biosynthesis of 2-Deoxy-scyllo-inosose in Metabolically Engineered Bacillus subtilis Recombinants - Lim, Joo Hyun; Hwang, Hyun Ha; Lee, Na Joon; Lee, Jae Woo; Seo, Eun Gyo; Son, Hye Bin; Kim, Hye Ji; Yoon, Yeo Joon; Park, Je Won (Frontiers in Microbiology, 2018)
2-Deoxy-scyllo-inosose (DOI) has been a valuable starting natural product for the manufacture of pharmaceuticals or chemical engineering resources such as pyranose catechol. DOI synthase, which uses glucose-6-phosphate (Glc6P) as a substrate for DOI biosynthesis, is indispensably involved in the initial stage of the biosynthesis of 2-deoxystreptamine-containing aminoglycoside antibiotics including butirosin, gentamicin, kanamycin, and tobramycin. A number of metabolically engineered recombinant strains of Bacillus subtilis were constructed here; either one or both genes pgi and pgcA that encode Glc6p isomerase and phosphoglucomutase, respectively, was (or were) disrupted in the sugar metabolic pathway of the host. After that, three different DOI synthase–encoding genes, which were artificially synthesized according to the codon preference of the B. subtilis host, were separately introduced into the engineered recombinants. The expression of a natural btrC gene, encoding DOI synthase in butirosin-producing B. circulans, in the heterologous host B. subtilis (BSDOI-2) generated approximately 2.3 g/L DOI, whereas expression of an artificially codon-optimized tobC gene, derived from tobramycin-producing Streptomyces tenebrarius, into the recombinant of B. subtilis (BSDOI-15) in which both genes pgi and pgcA are disrupted significantly enhanced the DOI titer: up to 37.2 g/L. Fed-batch fermentation by the BSDOI-15 recombinant using glycerol and glucose as a dual carbon source yielded the highest DOI titer (38.0 g/L). The development of engineered microbial cell factories empowered through convergence of metabolic engineering and synthetic biology should enable mass production of DOI. Thus, strain BSDOI-15 will surely be a useful contributor to the industrial manufacturing of various kinds of DOI-based pharmaceuticals and fine chemicals.